State disinvestment in higher education: The impact on public research universities' patent applications - Bo Zhao (Federal Reserve Bank of Boston, 2019)
While state appropriations are the largest revenue source of the U.S. public university systems, they have declined significantly over the past several decades. Surprisingly, there is little empirical work on the effect of state appropriation cuts on the research productivity of public universities. Helping fill that gap, this paper is the first to examine the role that state appropriations play in public universities' patent production. The results suggest that state appropriation cuts have a negative impact on the number of approved patent applications from public research universities. Lower state appropriations are shown to lead to a reduction in research expenditures, especially wages and salaries paid to research staff.
Keywords: H75; H77; I23; 330; state appropriations; state funding cuts; higher education; public universities; patent applications